2010
DOI: 10.1021/nn101926g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis Of Nitrogen-Doped Graphene Films For Lithium Battery Application

Abstract: We demonstrate a controlled growth of nitrogen-doped graphene layers by liquid precursor based chemical vapor deposition (CVD) technique. Nitrogen-doped graphene was grown directly on Cu current collectors and studied for its reversible Li-ion intercalation properties. Reversible discharge capacity of N-doped graphene is almost double compared to pristine graphene due to the large number of surface defects induced due to N-doping. All the graphene films were characterized by Raman spectroscopy, transmission el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
1,105
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,601 publications
(1,138 citation statements)
references
References 36 publications
29
1,105
2
2
Order By: Relevance
“…This was the fi rst evidence of the drawbacks of RGO binder-free electrodes. Indeed, it was subsequently found that, in absence of binder, the 1 st cycle irreversible specifi c capacity was always higher than 40% [37][38][39][40][41] and, in some cases, the binder-free electrodes were very fragile and diffi cult to handle. [ 41 ] Despite few research efforts starting the good practice of reporting the electrodes' active material loadings, [ 35,42 ] still the focus was only on gravimetric capacity, and no indication on volumetric values was given.…”
Section: Continuedmentioning
confidence: 99%
See 1 more Smart Citation
“…This was the fi rst evidence of the drawbacks of RGO binder-free electrodes. Indeed, it was subsequently found that, in absence of binder, the 1 st cycle irreversible specifi c capacity was always higher than 40% [37][38][39][40][41] and, in some cases, the binder-free electrodes were very fragile and diffi cult to handle. [ 41 ] Despite few research efforts starting the good practice of reporting the electrodes' active material loadings, [ 35,42 ] still the focus was only on gravimetric capacity, and no indication on volumetric values was given.…”
Section: Continuedmentioning
confidence: 99%
“…In 2010, the further progression of graphene-based host structures (i.e., hollow GO spheres, [ 43 ] RGO, [ 37,39,[44][45][46][47][48][49][50] unzipped CNT, [ 51 ] bottom-up-synthesized graphene, [ 52 ] CVD-synthesized graphene [ 40 ] and N-doped graphene [ 40 ] ) only enabled limited progresses (Table 1 ). However, some major advances in understanding the Li-ion storage mechanism in different kinds of graphene were reported.…”
Section: Continuedmentioning
confidence: 99%
“…In addition, the electronic and chemical properties of graphene can be modified by chemical doping heteroatoms, such as boron atoms and nitrogen atoms [11][12][13][14][15]. Particularly, nitrogen-doped graphene has been extensively applied in various fields, such as electrocatalysis [16,17], supercapacitor [18,19], Li-air fuel cell [20], and lithium-ion batteries [21][22][23][24]. Recently, nitrogen-doped graphene has been widely investigated and delivers better electrochemical performance than the pristine graphene [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…It is also observed that graphene offers nice hierarchal structures by simple growth of graphene on graphene and it further avoids the use of a binder (electrically non‐conductive in nature), thus bringing a flexible electrode structure that delivers higher performance due to its large surface area 105. Furthermore, it is found that heteroatom doping can improve the conductivity and electrochemical properties of graphene by breaking its electroneutrality 106, 107, 108. Further, heteroatom doping can significantly change the electronic structure and density of state, thus improving the interfacial energy storage and quantum capacitance of graphene 108, 109, 110.…”
Section: Advanced Electrode Nanostructures For Lithium‐based Batteriesmentioning
confidence: 99%